Strategies to Strengthen Financial Governance at Hotel Barbara Samosir in Support of Sustainable Tourism - Karina Silaen; Arisman Parhusip; Lasman Eddy Bachtiar; Winda Simanjuntak; Andreas Jorghy Parapat; Aji Prabowo (Outline Journal of Community Development, 2026)
Hotel Barbara Samosir is one of the accommodation service providers in the Lake Toba tourism area, playing a vital role in supporting the development of sustainable tourism. Despite its significant potential, initial observations indicate that the financial governance system implemented remains relatively simple and has not yet fully adopted the principles of transparency, accountability, and efficiency. This community service activity was conducted on May, 26–27, 2026, with the aim of strengthening the managerial capacity and financial governance of Hotel Barbara Samosir’s management team through training, mentoring, and the application of good financial governance principles. The partner involved in this program was the management of Hotel Barbara Samosir, consisting of financial staff, administrative staff, and the hotel owner. The implementation method included several stages: needs identification, training in preparing simple financial reports, mentoring in the implementation of digital financial applications, and evaluating the effectiveness of the activities. The results of the program showed a significant improvement in the staff’s understanding of the importance of systematic financial recording, operational cost efficiency, and the hotel’s readiness to adopt sustainable business practices. This activity demonstrates that strengthening financial governance is a fundamental step in developing a professional, transparent, and economically sustainable hospitality sector in the Samosir tourism area.